Effects of fiber intake on intestinal pH, transit, and predicted oral mesalamine delivery in patients with ulcerative colitis. Issue 6 (22nd November 2020) - Yao, Chu K; Burgell, Rebecca E; Taylor, Kirstin M; Ward, Mark G; Friedman, Antony B; Barrett, Jacqueline S; Muir, Jane G; Gibson, Peter R
Abstract: Background and Aim: Limited data are available on the effects of fermentable fiber in altering intestinal pH and transit to predict efficacy‐based delivery profiles of pH‐dependent mesalamine coatings in ulcerative colitis (UC). This study aimed to examine regional pH and transit after acute changes in fermentable fiber intake in quiescent UC patients and their effects on drug release systems. Methods: In a randomized, double‐blind study, 18 patients with quiescent UC and 10 healthy controls were supplied meals high (13 g) or low (≤ 2 g) in fermentable fiber and subsequently ingested a wireless pH‐motility capsule. After a ≥ 3‐day washout, they crossed over to the other diet. Measurements of intestinal pH and transit were used to predict drug release for the various pH‐dependent coatings. Results: Increasing fermentable fiber intake lowered overall (median 6.2 [6.1–6.7] vs low: 6.9 [range or interquartile range: 6.4–7.4]; P = 0.01) and distal pH (7.8 [7.3–8.1] vs 8.2 [8.0–8.5]; P = 0.04) in controls. In UC patients, only cecal pH was decreased (high: 5.1 [4.8–5.5] vs low: 5.5 [5.3–5.7]; P < 0.01). Colonic transit in the UC cohort varied widely after a low‐fiber intake but tended to normalize after the high fermentable fiber intake. Hypothetical coating dissolution profiles were heterogeneous in UC patients, with a multi‐matrix delayed release system having the highest likelihood of patients (20–40%) with incomplete dissolution, and predominant small intestinal dissolution predicted for Eudragit L (94% patients) and S (44–69%). Conclusions: Patients with quiescent UC have abnormalities in intestinal pH and transit in response to acute changes in fermentable fiber intake. These have potentially detrimental effects on predicted luminal release patterns of pH‐dependent 5‐aminosalicylic acid release systems.